2019
DOI: 10.1002/jcp.28957
|View full text |Cite
|
Sign up to set email alerts
|

miR‐4429 sensitized cervical cancer cells to irradiation by targeting RAD51

Abstract: Cervical cancer (CC) is a prevalent malignancy in women, with the feature of metastasis and easy recurrence is responsible for a large proportion of global cancer deaths. Radiotherapy is one of the common treatment tools for CC patients with unresectable tumors. However, radio-resistance in patients could be a major reason for recurrence. Therefore, it is of significance to tunnel the molecular mechanism of radio-resistance in CC. MicroRNAs (miRNAs) are increasingly reported in the regulation of cancer progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Furthermore, another study provided evidence that there is a negative correlation between miR-4429 levels and radioresistance in cervical cancer cells. Indeed, the up-regulation of miR-4429 improves the efficacy of irradiation by repressing RAD51, suggesting the possibility of using miR-4429 mimics to defeat radioresistance, one of the major causes of cancer recurrence [65] (Table 2).…”
Section: Mir-182-5p and Mir-4429mentioning
confidence: 99%
“…Furthermore, another study provided evidence that there is a negative correlation between miR-4429 levels and radioresistance in cervical cancer cells. Indeed, the up-regulation of miR-4429 improves the efficacy of irradiation by repressing RAD51, suggesting the possibility of using miR-4429 mimics to defeat radioresistance, one of the major causes of cancer recurrence [65] (Table 2).…”
Section: Mir-182-5p and Mir-4429mentioning
confidence: 99%
“…For instance, miR-152 expression is upregulated in the peripheral blood of patients with cervical intraepithelial neoplasia, serving as an early diagnostic and prognostic biomarker (18). Furthermore, miR-4429 sensitizes cervical cancer cells to irradiation via the targeting of RAD51 recombinase (19). Additionally, increasing evidence has demonstrated that the long non-coding (lnc)RNAs serve crucial roles in the migration, differentiation, invasion and proliferation of cells (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the anti-oncogenic role of miR-4429 has been confirmed in clear cell renal cell carcinoma [10]. Furthermore, miR-4429 was differentially downregulated in CC cells when compared to normal cells [11]. The potential role of miR-4429 in CC was further investigated in the current study.…”
Section: Introductionmentioning
confidence: 69%
“…Analogously, Wu et al reported that the overexpression of miR-4429 overturned the oncogenic role of LINC00313 in papillary thyroid cancer, revealing the anti-tumor role of miR-4429[23]. In addition, miR-4429 could increase the radio-sensitivity of CC cell, revealing the potential therapeutic potential of miR-4429 for CC patients[11].…”
mentioning
confidence: 86%